Evolutionary Conserved Function of Barley and Arabidopsis 3-KETOACYL-CoA SYNTHASES in Providing Wax Signals for Germination of Powdery Mildew Fungi. Issue 3 (8th September 2014) - Weidenbach, Denise; Jansen, Marcus; Franke, Rochus B.; Hensel, Goetz; Weissgerber, Wiebke; Ulferts, Sylvia; Jansen, Irina; Schreiber, Lukas; Korzun, Viktor; Pontzen, Rolf; Kumlehn, Jochen; Pillen, Klaus; et al.
Abstract : An orthologous pair of genes from barley and Arabidopsis is involved in long-chain fatty acid signaling that is required for germination of conidia from distantly related powdery mildews . Abstract: For plant pathogenic fungi, such as powdery mildews, that survive only on a limited number of host plant species, it is a matter of vital importance that their spores sense that they landed on the right spot to initiate germination as quickly as possible. We investigated a barley ( Hordeum vulgare ) mutant with reduced epicuticular leaf waxes on which spores of adapted and nonadapted powdery mildew fungi showed reduced germination. The barley gene responsible for the mutant wax phenotype was cloned in a forward genetic screen and identified to encode a 3-KETOACYL-CoA SYNTHASE ( HvKCS6 ), a protein participating in fatty acid elongation and required for synthesis of epicuticular waxes. Gas chromatography-mass spectrometry analysis revealed that the mutant has significantly fewer aliphatic wax constituents with a chain length above C-24. Complementation of the mutant restored wild-type wax and overcame germination penalty, indicating that wax constituents less present on the mutant are a crucial clue for spore germination. Investigation of Arabidopsis ( Arabidopsis thaliana ) transgenic plants with sense silencing of Arabidopsis REQUIRED FOR CUTICULAR WAX PRODUCTION1, the HvKCS6 ortholog, revealed the same germination phenotype against adapted and nonadapted powdery mildew fungi. Our findings hint to an evolutionary conserved mechanism for sensing of plant surfaces among distantly related powdery mildews that is based on KCS6 -derived wax components. Perception of such a signal must have been evolved before the monocot-dicot split took place approximately 150 million years ago.